2016
DOI: 10.1007/s00425-016-2536-0
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species and hormone signaling cascades in endophytic bacterium induced essential oil accumulation in Atractylodes lancea

Abstract: Pseudomonas fluorescens induces gibberellin and ethylene signaling via hydrogen peroxide in planta . Ethylene activates abscisic acid signaling. Hormones increase sesquiterpenoid biosynthesis gene expression and enzyme activity, inducing essential oil accumulation. Atractylodes lancea is a famous Chinese medicinal plant, whose main active components are essential oils. Wild A. lancea has become endangered due to habitat destruction and over-exploitation. Although cultivation can ensure production of the medici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Its bioactive component, the sesquiterpenoids, possesses various pharmacology properties such as antibacterial, antitumour, and immunomodulation abilities (Wang et al, 2008; Koonrungsesomboon et al, 2014; Na-Bangchang et al, 2017). Over the past few years, natural sources of A. lancea have been in short supply because of the excessive exploitation and slow growth rate of the herb (Zhou et al, 2016). The medicinal source of A. lancea mainly derives from artificial cultivation, but the yield and quality of this herb are relatively low (Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its bioactive component, the sesquiterpenoids, possesses various pharmacology properties such as antibacterial, antitumour, and immunomodulation abilities (Wang et al, 2008; Koonrungsesomboon et al, 2014; Na-Bangchang et al, 2017). Over the past few years, natural sources of A. lancea have been in short supply because of the excessive exploitation and slow growth rate of the herb (Zhou et al, 2016). The medicinal source of A. lancea mainly derives from artificial cultivation, but the yield and quality of this herb are relatively low (Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, natural sources of A. lancea have been in short supply because of the excessive exploitation and slow growth rate of the herb (Zhou et al, 2016). The medicinal source of A. lancea mainly derives from artificial cultivation, but the yield and quality of this herb are relatively low (Zhou et al, 2016). At present, it is urgent to improve the quality and quantity of the herb as the market demand for A. lancea is increasing on a daily basis.…”
Section: Introductionmentioning
confidence: 99%
“…In Salvia miltiorrhiza hairy roots, Pseudomonas significantly improved tanshinone content via the improved activity of enzymes involved in the tanshinone biosynthetic pathway [8]. Pseudomonas fluorescens increased essential oil accumulation in Atractylodes lancea by increasing the activity of enzymes involved in sesquiterpenoid biosynthesis [38]. Thus, our results indicate several endophytic bacteria’s role in the metabolism of sesquiterpenoids.…”
Section: Discussionmentioning
confidence: 77%
“…In other cases, the inoculation of bacterial endophytes, previously isolated by the roots of W. somnifera, has increased the withanolide content in plant tissue during Alternaria alternata pathogenicity and upregulated the genes involved in withanolide biosynthetic pathways in both leaves and roots [54,59]. In another case, the bacterial endophytic P. fluorescens strain was able to enhance the accumulation of EOs in Atractylodes lancea through molecular signaling involving hydrogen peroxide, gibberellin, ethylene, and abscisic acid [60]. The same authors have also demonstrated that this strain of P. fluorescens induces a high production of medicinal sesquiterpenoid in A. lancea [61].…”
Section: Studies On the Role Of Mp-endophyte Interaction In The Produmentioning
confidence: 99%